Description of Lutzomyia (Pifanomyia) robusta n. sp. (Diptera, Psychodidae, Phlebotominae) from Peruvian Equadorean interandean areas - Eunice A. Bianchi Galati; Abraham G. Cáceres; Francois Le Pont (Universidade de São Paulo, 1995)
Description of Lutzomyia robusta, n. sp. (Diptera, Psychodidae, Phlebotominae) from interandean areas of Peru and Equador. Lutzomyia robusta, n. sp., probable vector of human bartonellosis and cutaneous leishmaniasis, is described and illustrated. This species presents strong affinity with L. serrana (Damasceno & Arouck, 1949) but they can be distinguished by variance analysis of four male characteristics and only one female characteristic. In the variance analysis, populations of L. serrana, of Amazonian areas of Brazil, Peru and Bolivia, the coast of Equador and other areas of Brazil were studied. The synonymy of Lutzomyia guayasi (Rodriguez) and L. serrana was corroborated. Descreve-se Lutzomyia (Pifanomyia) robusta, sp.n., provável vetora de bartonelose e leishmaniose tegumentar, de ocorrência em vales interandinos no Peru e Equador e que apresenta estreita afinidade com L. serrana (Damasceno e Arouck). A separação de ambas foi possível, por meio de análise de variância de alguns caracteres do macho e apenas um da fêmea. Na análise de variância, foram estudadas populações de L. serrana da região amazônica do Brasil, Peru e Bolívia; costa do Equador; região atlântica e outras áreas do Brasil. Corrobora-se a sinonímia de Phlebotomus guayasi Rodríguez com L. serrana.